Pre‐fire grazing and herbicide treatments can affect post‐fire vegetation in a Great Basin rangeland. Issue 1 (7th March 2023) - Gornish, Elise S.; Guo, Jessica S.; Porensky, Lauren M.; Perryman, Barry L.; Leger, Elizabeth A.
Abstract: Management of wildfire associated with spread of the highly invasive annual grass Bromus tectorum (cheatgrass) is a critical need in the western U.S. We investigated the utility of coupling common rangeland management strategies pre‐fire to modify post‐fire plant community outcomes. We used a long‐term, large‐scale experiment to test the separate and combined effects of pre‐fire targeted grazing (spring and fall), native plant seeding (seeding rate, seed coating and spatial seeding arrangement) and herbicide (glyphosate followed by 2 years of imazapic) on post‐fire plant community outcomes in a highly invaded system in the Great Basin, U.S. We found grazing and herbicide effects were consistent across cheatgrass biomass, count, and cover. Spring grazing reduced cheatgrass more effectively than fall grazing; however, this effect was detected primarily outside of the seeding treatments. Herbicide overall and in conjunction with grazing reduced cheatgrass and fuel loads. Among seeding treatments, seed mixtures proved more effective than monocultures for reducing both cheatgrass count and cover, particularly when combined with low seed rate. However, many seeding approaches resulted in higher cheatgrass dominance, and thus higher fuel loads. This work suggests that effects of pre‐fire herbicide for reducing cheatgrass abundance can persist post‐fire. Grazing, however, might not produce consistent results, and season of grazing can affect outcomes. Employing pre‐fire management strategies to interrupt the cheatgrass‐fire cycle may have utility. Some of our treatments were able to reduce cheatgrass abundance after fire, but despite our intensive interventions, we did not find a strategy that led to full restoration of native perennial species. Abstract : This work suggests that effects of pre‐fire herbicide for reducing cheatgrass abundance can persist post‐fire. Grazing, however, might not produce consistent results, and season of grazing can affect outcomes. Employing pre‐fire management strategies to interrupt the cheatgrass‐fire cycle may have utility.